2020
DOI: 10.1098/rsbl.2020.0081
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic allometry and vocal learning in mammals

Abstract: Acoustic allometry is the study of how animal vocalizations reflect their body size. A key aim of this research is to identify outliers to acoustic allometry principles and pinpoint the evolutionary origins of such outliers. A parallel strand of research investigates species capable of vocal learning , the experience-driven ability to produce novel vocal signals through imitation or modification of existing vocalizations. Modification of vocalizations is a common feature fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 90 publications
(146 reference statements)
2
26
2
Order By: Relevance
“…Unfortunately, the relative contribution of both sound production mechanisms is unclear. Here, we provide support for a hypothesis trying to segregate anatomical vs. learning mechanisms (Garcia & Ravignani, 2020;Ravignani & Garcia 2021). We find that harbour seals are mechanistically constrained by their vocal anatomy, and their large vocal flexibility (Ralls et al, 1985;Borda et al, in press) thus points towards extensive volitional control over their vocalisations.…”
Section: Discussionsupporting
confidence: 79%
“…Unfortunately, the relative contribution of both sound production mechanisms is unclear. Here, we provide support for a hypothesis trying to segregate anatomical vs. learning mechanisms (Garcia & Ravignani, 2020;Ravignani & Garcia 2021). We find that harbour seals are mechanistically constrained by their vocal anatomy, and their large vocal flexibility (Ralls et al, 1985;Borda et al, in press) thus points towards extensive volitional control over their vocalisations.…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, we maintain the plausibility of such a scenario, however, as even the simplest (monotonic) rhythms still appear to occur more frequently in terrestrial rather than arboreal primate species (Table 6). Furthermore, it is worth emphasizing that artificially deep tones, as some other mammals produce (Garcia and Ravignani, 2020), are vastly more readily enabled via hominin bipedality by virtue of free-to-drum arms and hands. Being terrestrial also likely enabled hominins to use the ground as a sturdy and unyielding acoustic platform, permitting even more vigorous striking of inanimate, and perhaps resonant, objects-such as hollow logs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that elaborate control over the vocal apparatus provides a biophysical mechanism for vocal learning. Thus, laryngeal plasticity and vocal flexibility may provide indirect evidence for vocal learning in harbour seals' puppyhood [ 28 , 38 , 75 ].…”
Section: Discussionmentioning
confidence: 99%